INTEGRASI BUDAYA, PENDIDIKAN, DAN POLITIK DALAM DAKWAH NAHDLATUL WATHAN DI LOMBOK: ANALISIS MENDALAM TERHADAP KONTRIBUSI TGH. MUHAMMAD ZAINUDDIN ABDUL MADJID - Herman Zuhdi (Jurnal Cakrawala Ilmiah, 2025)
Nahdlatul Wathan (NW), founded by Tuan Guru Haji (TGH) Muhammad Zainuddin Abdul Madjid in 1953 in Lombok, is one of the most influential religious organizations in Indonesia, particularly in the Lombok region. Although it holds a minority position nationally compared to Nahdlatul Ulama (NU) and Muhammadiyah, NW has succeeded in becoming a majority organization. This article aims to analyze TGH Zainuddin's approach to da'wah that integrates cultural, educational, and political aspects in all of NW's da'wah activities. Through a qualitative research approach, information and data were obtained from various literature sources as well as interviews with local community leaders. The analysis results indicate that this integrative approach enables NW to gain significant support from the wider community and expand its reach.